Impact drills jump back and lateral refraction in explosive muscle force development working background among goalkeepers - Abdul Sahib, Mounir (Journal of Physical Education, 2019)
leave enable problem noted researcher of goalkeepers and privacy requirements, capabilities and skills especially in the preparation of the guards and especially explosive strength and explosive strength importance through the diverse skills of jumping front & side and back is one of the most important capabilities that must be owned by and through the work of researcher goalkeeping coach and through control of goalkeepers in their matches found that goalkeepers have power jumped forward seamlessly, however, jumping backward and vulnerable witness profile compared to the jumping front use Researcher of experimental method and sample search way intentional style of one sample of (6) keepers and researcher with the modified test horizontal jumping forward and prepare exercises to develop explosive power with jump and side boxes and balls using medical bag statistics (SPSS) the researcher concluded that the use of training jump.Side and reverse their explosive capacity of   muscle background and development level of the explosive capacity of the muscles on the left side and right side have goalkeeper junior